An Analysis Of Figurative Expression in English Translation Of Prophetic Tradition In Shahih Muslim : A Cultural Perspective - PURNAMA, YOGA (2012)
The objectives of the study are (1) to describe the types of figurative language found in Shahih Muslim (2) to describe the types of meaning used in figurative expression of prophetic tradition found in Shahih Muslim. (3) to describe the implied meaning of figurative expression in Prophet Muhammad's utterances reflected in Shahih Muslim by using cultural perspective The type of this research is qualitative research. In collecting the data, the writer uses documentation method by selecting the figurative languages which can be found in English translation of Shahih Muslim taken from Islam-download website, especially in the Book of Faith (http://islam-download.site90.net/ download.html). To achieve the objectives, the writer classifies data based on Perrine's theory and applies cultural perspective of Arab by Philip K. Hitti to reveal and describe the meaning. The result of the study shows that regarding to the (1) types of figurative languages the writer found the types of figurative as follows: Synecdoche, Personification, Allegory, and Simile. (2) type of meaning used in the figurative expression are: Grammatical meaning, Textual meaning, and Situational meaning. (3) implied meaning of the prophet Muhammad's utterances are: Explaining, Describing, and Reminding. Key word : Figurative language, prophetic tradition, cultural perspective